2011
DOI: 10.1007/s00428-011-1177-8
|View full text |Cite
|
Sign up to set email alerts
|

Management of precancerous conditions and lesions in the stomach (MAPS): guideline from the European Society of Gastrointestinal Endoscopy (ESGE), European Helicobacter Study Group (EHSG), European Society of Pathology (ESP), and the Sociedade Portuguesa de Endoscopia Digestiva (SPED)

Abstract: Atrophic gastritis, intestinal metaplasia, and epithelial dysplasia of the stomach are common and are associated with an increased risk for gastric cancer. In the absence of guidelines, there is wide disparity in the management of patients with these premalignant conditions. The European Society of Gastrointestinal Endoscopy, the European Helicobacter Study Group, the European Society of Pathology, and the Sociedade Portuguesa de Endoscopia Digestiva have therefore combined efforts to develop evidence-based gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
223
0
10

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(240 citation statements)
references
References 249 publications
(269 reference statements)
7
223
0
10
Order By: Relevance
“…Some studies have indicated that LGD and HGD should be treated, because genomic instability may already be present [49][50][51][52]. However, the European guidelines recommend reassessment with biopsy sampling and surveillance at 6-month to 1-year intervals for patients with HGD in the absence of endoscopically defined lesions [8]. According to whether there is evidence of invasion, there is a potential risk of underdiagnosing a lesion as LGD or HGD, even if it is submucosal or advanced GC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have indicated that LGD and HGD should be treated, because genomic instability may already be present [49][50][51][52]. However, the European guidelines recommend reassessment with biopsy sampling and surveillance at 6-month to 1-year intervals for patients with HGD in the absence of endoscopically defined lesions [8]. According to whether there is evidence of invasion, there is a potential risk of underdiagnosing a lesion as LGD or HGD, even if it is submucosal or advanced GC.…”
Section: Discussionmentioning
confidence: 99%
“…There are no universally accepted criteria for invasive growth into the lamina propria [16]. Therefore, histological findings of invasion are defined according to the World Health Organization (WHO) classification and European management guidelines as follows: invasion into the muscularis mucosa or submucosa; lymphovascular invasion; infiltration of the stroma by single cells; small clusters of cells (small nest); small gland formation, and marked glandular crowding; excessive branching, budding, and a trabecular pattern; fused glands, cribriform glands; stromal response (desmoplasia) [6,8]. For objective evaluation of invasion in this study, the Vienna Classification was used (Table 1) [9].…”
Section: Western Diagnostic Criteriamentioning
confidence: 99%
“…3 9 "Management of precancerous conditions and lesions in the stomach" (MAPS ) Guidelines der Europäischen Gesellschaft für Gastrointestinale Endoskopie (ESGE) und Europäischen Gesellschaft für Pathologie (ESP). Adaptiert nach [9] Abb. 4 8 Tubuläres Adenom des Magens (intestinaler Typ), geringgradige intraepitheliale Neoplasie.…”
Section: Gastraler Typ (Pylorusdrüsen-adenom)unclassified
“…Soon after this, all attention turned to this novel pathogen. Over last three decades, tremendous progress has been made to understand its biology [8][9][10], epidemiology [11][12], pathogenicity [13], treatment [14][15][16][17][18], and laboratory diagnosis [19][20][21][22]. The number of peer-reviewed articles on H. pylori is still growing (Figure 1).…”
Section: Introductionmentioning
confidence: 99%